2019
DOI: 10.1021/acs.jpcc.9b05090
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Effects on the Diffusivity of Hydrogen Isotopes in Zeolites

Abstract: The molecular sieving of H2 and its isotopes produced by nuclear plants is a long-standing research where some adsorption processes are well identified. However, some mechanisms governing the diffusion of the proton and its isotopes within a faujasite NaX at low temperatures (40–100 K) are still troublesome to characterize. Notwithstanding, an understanding of the processes governing adsorption diffusion within narrow pores is essential for the development of recycling procedures of gases produced by nuclear p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Concerning the zeolites, several molecular simulations of adsorption and diffusion of hydrogen and deuterium are described in the literature [22][23][24][25][26][27] . They have been performed with Monte Carlo or Molecular Dynamics methods using different force fields including the Feynman-Hibbs variational approach to take into account quantum effects.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the zeolites, several molecular simulations of adsorption and diffusion of hydrogen and deuterium are described in the literature [22][23][24][25][26][27] . They have been performed with Monte Carlo or Molecular Dynamics methods using different force fields including the Feynman-Hibbs variational approach to take into account quantum effects.…”
Section: Introductionmentioning
confidence: 99%
“…To date, however, only a few MOFs have been utilized to investigate the application of diffusivity to gas separation either experimentally (e.g., pulsed-field-gradient (PFG) NMR and quasi-elastic neutron scattering (QENS)) or through molecular dynamic simulations. [8][9][10][11] Stallmach et al used PFG NMR to study the diffusion of hydrocarbons, such as methane, ethane, n-hexane, and benzene, in MOF-5 and revealed for the first time the diffusivity correlation between the surface area and the pore size. [8] Similarly, Pusch et al explored CO 2 and CH 4 self-diffusion in ZIF-8 at elevated pressure and found that the former diffuses slightly faster than the latter.…”
mentioning
confidence: 99%
“…23 In the present study, we use a primitive rhombohedral cell of FAU containing around 165 atoms to reduce computational effort. [24][25][26][27] It can be seen in Figure 1 that the primitive cell of faujasite contains two supercages and eight hexagonal windows connecting the sodalite with the supercage. 25,28 Please do not adjust margins Please do not adjust margins Interaction energies have been calculated according to the following equation:…”
Section: Dft Calculationsmentioning
confidence: 99%